Selecting Green Suppliers Using a Hybrid Fuzzy BWM and IVIF-MABAC Approach in the Tropical Fruit Sector - Dana Marsetiya Utama; Krisna Hayu Dirgantara (Politeknik APP Jakarta, 2026)
Agribusiness companies face challenges in green supplier selection due to subjective judgments and information gaps. To address these linguistic ambiguity and subjective uncertainties, this study develops a hybrid MCDM framework integrating the α-cut based Fuzzy BWM and Interval-Valued Intuitionistic Fuzzy MABAC (IVIF-MABAC). F-BWM α-cut derives stable weights from linguistic preferences, and IVIF-MABAC provides robust ranking by handling hesitancy. This approach, novel for the Indonesian tropical fruit sector, involved three experts (academic, manager, consultant) via questionnaires and FGDs. Results show Product Quality and Transparency & Traceability are critical. The 4th Green Supplier consistently achieved the highest ranking. The framework offers managers a reliable tool, enhancing sustainability and competitiveness within tropical fruit supply chains.